It could still be a lake - Fowler, Allan (New York : Children's Press, 1996)
Simple text and illustrations describe the characteristics, origin, and pollution of lakes.
Includes index.
3.2
K-3
Keywords: Lakes -- Juvenile literature; Lakes; Lakes